5C Principles in Profit and Loss Sharing Financing on Baitul Maal Wattamwil as Islamic Micro Finance In Indonesia - Thalib, Prawitra; Hajati, Sri; Kurniawan, Faizal; Aldiansyah, Komari (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2020)
Baitul Maal wat Tamwil is a financial institution with a sharia concept that was born as a choice that changes the concept of maal and tamwil in one institution. The concept of maal was born and became part of the lives of Muslim communities in terms of collecting and distributing funds for zakat, infaq and shadaqah) productively. While the Tamwil concept was born for purely business activities to benefit from the middle to micro sectors of society. One of the financing activities carried out by BMT is financing based on profit sharing principles. Profit sharing is done by two types with mudharabah and musyarakah contracts. musyarakah is derived from the word syirkah, also called syarikah, which means a cooperation agreement between two or more parties for certain businesses, each party providing the assistance fund, and will be borne together in accordance with the aid fund, or mutual agreement. The methods used in the writing of this article are normative research using a statute approach and a conceptual approach.the result of this research indicates distribution of funds or financing must pay attention to various matters relating to caution both from within and from outside the Islamic Financial Institutions of Islamic Banks and Non-Islamic Banks. Matters issued from internships are in the form of Legal Lending Limit (LLL), financing guidelines, operational aspects. Aside from internal, things that are of caution are also excluded from the external supported by 5C analysis (Character, Condition, Capacity, Capital, Guarantee) and sharia compliance). This analysis must be considered in channeling financing to avoid elements forbidden in Islam.